2017
DOI: 10.1186/s13071-017-2510-0
|View full text |Cite
|
Sign up to set email alerts
|

Hap2, a novel gene in Babesia bigemina is expressed in tick stages, and specific antibodies block zygote formation

Abstract: BackgroundBovine babesiosis is a tick-borne disease caused by the protozoan parasites of the genus Babesia. In their host vector, Babesia spp. undergo sexual reproduction. Therefore, the development of sexual stages and the subsequent formation of the zygote are essential for the parasite to invade the intestinal cells of the vector tick and continue its life-cycle. HAP2/GCS1 is a protein identified in plants, protozoan parasites and other organisms that has an important role during membrane fusion in fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…As a result, in vivo induction of sexual stages would be expected to occur non-synchronously and the rise and fall of ccp expression would be masked. In addition to ccp2 and ccp3 , expression of hap2 , a gene found to be important in B. bovis sexual stage development [ 16 ], was upregulated at 6 h but, unlike the expression pattern of the ccp genes, remained elevated at 15 and 24 h after TCEP induction (Additional file 2 : Figure S2), consistent with a previous study [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As a result, in vivo induction of sexual stages would be expected to occur non-synchronously and the rise and fall of ccp expression would be masked. In addition to ccp2 and ccp3 , expression of hap2 , a gene found to be important in B. bovis sexual stage development [ 16 ], was upregulated at 6 h but, unlike the expression pattern of the ccp genes, remained elevated at 15 and 24 h after TCEP induction (Additional file 2 : Figure S2), consistent with a previous study [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…The results represent the means of three experiments, each containing three technical replicates. In addition to the ccp genes, we examined the expression of B bigemina hap2 (BBBOND_0307410) in TCEP-induced parasites and found it was upregulated at 6, 15 and 24 h (Additional file 2 : Figure S2) as previously demonstrated [ 13 ]. Additionally, we confirmed polypeptide expression of CCp2 and CCp3 by IFA using a set of previously characterized polyclonal antibodies [ 12 ].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Amongst numerous putative microgamete-specific transcripts in our data, the one coding for a microgamete-specific gamete fusion protein, HAP2, particularly drew our attention because of its relatively well-defined localisation in microgametes, its role in membrane fusion leading to fertilisation and zygote formation in Plasmodium 41,42 and Babesia 43,44 , and its prominence in the microgamete transcriptome of E . tenella 15 , all of which underscores its vital, conserved function in sexual reproduction in the Apicomplexa 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Bohaliga et al [11] identified BBBOND_0204030 as a gene uniquely transcribed by B. bigemina tick stages and by in vitro induced B. bigemina sexual stages. The B. bigemina HAP2 protein, that is associated with the development of gametes in apicomplexan parasites [12], was found to be expressed by parasite stages developing in the midgut of infected ticks at day 3 post-repletion of female R . microplus ticks.…”
Section: Introductionmentioning
confidence: 99%